SEMINAR EDUKASI PENGGUNAAN EMAIL DAN KEAMANAN SIBER BAGI SISWA SMPN 1 NONGGUNONG - Syirva Nada Fidya; Diana Uzlifatul Khairu Ummah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
The rapid development of information technology demands that the younger generation, including junior high school students, have a good understanding of how to use digital media safely and responsibly. This seminar aims to provide education on the effective use of email and raise students' awareness about the importance of cybersecurity. The activity was held at SMPN 1 Nonggunong, involving seventh-grade students. The topics covered included the basics of using email, digital communication etiquette, and potential cybersecurity threats such as phishing, malware, and personal data breaches. The implementation methods included material presentations, interactive discussions, and case simulations. The evaluation results showed an 85% improvement in students' understanding of digital security practices, based on pre-test and post-test assessments. This aligns with the findings of Andria et al. (2024), which state that cybersecurity training effectively enhances students' digital literacy. This seminar also supports the research of Giap et al. (2024), which emphasizes the importance of interactive education in increasing digital awareness among teenagers. It is hoped that similar activities can be conducted on a sustainable basis as part of the school's digital literacy curriculum, given the importance of instilling online security practices from an early age.